A Comprehensive Account of Fishing Crafts and Gears of River Tapti, India - S. P. Kamble; Bhakta, Dibakar; W. A. Meetei; Vaisakh G; J. K. Solanki; S. K. Koushlesh; T. N. Chanu; B. K. Behera; V. R. Suresh; S. Samanta; B. K. Das (Fishery Technology, 2022)
The study aimed at cataloging fishing crafts and gears operated in the 724 km stretch of the river Tapti and seasonal variations in its operations during the period 2017-2020. A total of five fishing crafts and ten gears were listed. The fishing crafts include inflated motor vehicle tubes, boat (non-mechanized), dugout canoe, raft on the tube, catamaran, and thermocol platform. The fishing gears include gill net, cast net, mahajal (dragnet), mosquito net (dragnet), hook and line, pole and line, saree, traps (crab and prawn trap), push net (pelni), and long handle scoop net (jhelki). Gillnet was found to be the only dominant fishing gear (66-78%) while other gears contributed more or less uniformly; the inflated tubes (61 – 83%) and boats (11 – 32%) were observed as major fishing crafts used along the entire length of the river and during all seasons. The species composition, CPUE, cost of crafts and gears, durability, etc. were also documented along with the seasonal and stretch-wise variations in its operations. The present documentation indicated that despite modernization in fisheries sectors, traditional and indigenous crafts and gears were operated along the entire river. Lack of sustainability in the fishing practices and absence of knowledge on improved efficiency in fishing efforts were evident in the major portion of the river stretch.